THE ROLE OF TAX STIMULATION IN THE SYSTEM OF STATE SUPPORT FOR INDUSTRIAL ENTERPRISES - S. K. Khamirzova; A. U. Ushkho (Новые технологии, 2020)
The relevance of the research is due to the need to improve the mechanism of state financial support for industrial production in the framework of stimulating the innovative development of the economy. The subject of the research is tax incentives for enterprises in the system of state financial support for industrial production.The purpose of the research is development of measures to improve the efficiency of tax incentive instruments for industrial enterprises based on the assessment of their effectiveness in modern conditions.When the national economy is unstable due to international sanctions against Russia, as well as internal factors, the need to form a core of industrial production capable of ensuring economic growth through the introduction of advanced technologies is of particular importance. In this regard, the article systematizes state measures aimed at supporting the activities of industrial enterprises used in the Russian economy and in the Republic of Adygea, in particular. The best foreign experience in tax incentives for industrial production in comparison with the Russian model of applying tax incentives has been summarized; tax expenses of the budgets of the budget system of the Russian Federation by types of taxes and types of state programs related to the development of industry have been analyzed; priority measures have been developed to reduce the tax burden of industrial enterprises.